Mechanical performance and design optimisation of metal honeycombs fabricated by laser powder bed fusion - Afkhami Shahriar; Amraei Mohsen; Gardner Leroy; Piili Heidi; Wadee M.Ahmer; Salminen Antti; Björk Timo (ELSEVIER SCI LTD, 2022)
Honeycomb structures have a wide range of applications, from medical implants to industrial components. In addition, honeycombs play a critical role when passive protection is required due to their low density and high energy absorption capabilities. With the transition of additive manufacturing from a rapid prototyping approach to a manufacturing process, this technology has recently offered designers and manufacturers the ability to fabricate and modify lattice structures such as honeycombs. The current study presents the application of laser powder bed fusion, a common additive manufacturing process for producing industrial metal components, for fabricating metal honeycombs. In addition, this study examines three modified designs that can only be practically fabricated using additive manufacturing and compares them with conventional honeycombs. For this purpose, quasi-static and dynamic compression tests are conducted to evaluate and compare the performance of the honeycomb structures. The results show that the structures produced by additive manufacturing have acceptable performance compared to conventional honeycomb structures, and laser powder bed fusion can be considered to be a reliable manufacturing method for honeycomb production. Furthermore, the honeycombs produced according to the modified designs generally outperformed their counterparts made from the typical hexagonal cells. Ultimately, the use of triangular cells as a design modification is proposed to produce honeycombs with promising performance characteristics in all of their principal axes and under various pressure scenarios, from quasi-static to dynamic loading rates. Finally, this study also investigates the applicability of a newly developed maraging steel for additive manufacturing of honeycombs. Microstructural analysis and quasi-static tensile tests have confirmed the material properties for this purpose.